PERUBAHAN BENTUK FISIK BALE WANTILAN SEBAGAI FUNGSIPENUNJANG KOMPLEK PARAHYANGAN - I Kadek Arya Adi Wirawan; Bagus Made Arjana; Desak Made Sukma Widiyani (Universitas Dwijendra, 2016)
Bale Wantilan is a building that is open in all directions without being limited wall that has a roof bertumpang. Bale Wantilan referred to in this study is Bale wantilan who are still using the original patterns of traditional Balinese architecture. That is built on the principles enshrined in the palm and palm Asta Asta Kosala Kosali Bhumi. Generally set up Bale wantilan during set up and after the establishment of complete, followed by the process steps in line with the ceremonial work steps. After building completion ceremony